Licensing of Sewer Root Control Pesticide Applicators in Florida - Frederick M. Fishel (EDIS)
PI-146, a 3-page fact sheet by Frederick M. Fishel, explains the licensing and regulation of persons who apply restricted use pesticides to control or prevent the growth of roots in sewer lines or pipes in Florida. Published by the UF Pesticide Information Office, February 2007.